The Use of Mortgage Covered Bonds - Avesani, Renzo (IMF Working Papers; Working Paper ;, 2007)
The rapid mortgage credit growth experienced in recent years in mature and emerging countries has raised some stability concerns. Many European credit institutions in mature markets have reacted by increasing securitization, particularly via mortgage covered bonds. From the issuer's perspective, these instruments have become an attractive funding source and a tool for assetliability management; from the investor's perspective, covered bonds enjoy a favorable risk-return profile and a very liquid market. In this paper, we examine the two largest "jumbo" covered bond markets, Germany and Spain. We show how movements in covered bond prices can be used to analyze the credit developments of the underlying issuer and the quality of its mortgage portfolio. Our analysis also suggests that mortgage covered bonds could be of interest to other mature and emerging markets facing similar risks related to mortgage credit.